Tonicity-independent regulation of the osmosensitive transcription factor TonEBP (NFAT5) - Halterman, Julia A. (American Physiological Society, 2012)
Tonicity-responsive enhancer binding protein (TonEBP/nuclear factor of activated T-cells 5 [NFAT5]) is a Rel homology transcription factor classically known for its osmosensitive role in regulating cellular homeostasis during states of hypo- and hypertonic stress. A recently growing body of research indicates that TonEBP is not solely regulated by tonicity, but that it can be stimulated by various tonicity-independent mechanisms in both hypertonic and isotonic tissues. Physiological and pathophysiological stimuli such as cytokines, growth factors, receptor and integrin activation, contractile agonists, ions, and reactive oxygen species have been implicated in the positive regulation of TonEBP expression and activity in diverse cell types. These new data demonstrate that tonicity-independent stimulation of TonEBP is critical for tissue-specific functions like enhanced cell survival, migration, proliferation, vascular remodeling, carcinoma invasion, and angiogenesis. Continuing research will provide a better understanding as to how these and other alternative TonEBP stimuli regulate gene expression in both health and disease.